Information exchange patterns and technology adoption behavior of cattle farmers in the Colombian Amazon - Lienert, Anja; Lippert, Christian; Burkart, Stefan (International Center for Tropical Agriculture, 2023)
Colombia's cattle sector, characterised by extensive production systems, plays an important role in the national economy, contributing 19.8% to the agricultural GDP and providing employment and income to around one million people. However, the sector is associated with low productivity and negative environmental impacts such as land degradation, greenhouse gas emissions, and deforestation. This is particularly true in the Caquetá Department, located in the Colombian Amazon, which has the country's fifth largest cattle herd and the highest deforestation rate. Although efforts have been made in recent decades to introduce improved production practices to intensify cattle farming in a sustainable manner (e.g., improved forages or silvo-pastoral systems), corresponding adoption rates remain low.